Modeling relationships of matriculation students' affective and cognitive factors and achievement in organic chemistry - Othman, Azraai (2016)
Modeling the learning of organic chemistry among matriculation students requires the integration of cognitive and affective factors and students’ performance. The cognitive factors include spatial ability and prior conceptual knowledge, whereas affective factors involve student attitude and self-efficacy. This study reviews Novak’s Model of Education that is relevant to the need for learning in organic chemistry. The literature reviews the importance of cognitive and affective factors that influence students’ achievement in organic chemistry. This study explores the integration of cognitive and affective factors using Structural Equation Modeling (SEM) analysis. Models was developed and validated through the correlational relationships among factors using student responses regarding Attitude towards Organic Chemistry Questionnaire (ATOCQ), The Purdue Visualization of Rotations Test (ROT), Chemistry Conceptual Inventory (CCI), and Organic Chemistry Achievement Test (OCAT).